The Effect of Education about Cervical Cancer through Zoom Meetings on the Knowledge of Adolescent Girls in 1 Lumbung High School - Yanti Srinayanti; Iin Marlina; Sri Utami Asmarani (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background: Cervical cancer ranks first after breast cancer in developing countries, one of which is in Indonesia. Cervical cancer is a sexually transmitted disease that originates from a viral infection, namely the human papilloma virus which stimulates changes in the behavior of cervical epithelial cells. The prevalence of women against cervical cancer is large because of the tendency for women to marry at a young age and the limited economic capacity that makes access to information limited. The provision of health education through zoom meetings considering the limitations due to the pandemic is very necessary for teenagers as a preventive effort considering that at the age of teenagers they are very vulnerable to having free sex. Objective: The effect of education through a zoom meeting on cervical cancer on the knowledge of young women in SMA Negeri 1 Lumbung in March 2022. The research used is a quantitative study. Methods: a tool for data collection using a questionnaire while the total sampling technique with a sample of 40 students. Results: The results of data analysis using a t-test on the effect of education through zoom meetings on cervical cancer obtained a significant value because the value of t count > t table = 15,627 > 2,023 and the value of > p value = 0.05 > 0.000. Conclusion: from the results of the study, it can be concluded that there is a significant effect of health education between before being given health education and after being given health education.